Influential Effect of Diet and Panchakarma Therapy in Liver Disease: A Case Study Especially Referencing to the Vataja Yakrita Vikara - Acharya Manish; Gitika Chaudhary; Richa; Siddharth Charan; Tanu Rani (International Journal of Ayurveda and Pharma Research, 2025)
Ayurveda can offer promising improvement in liver diseases within a short period of time. Currently, there is a rapid rise in chronic liver disease (CLD) cases due to factors like alcohol intake, viral infections, and poor dietary habits. The most common cause nowadays is a long-term unhealthy lifestyle. In Ayurveda, Yakrit Vikara are described across various chapters and are considered disorders of Raktavaha Srotas. As the liver plays a key role in digestion and metabolism, liver disorders often present with digestive symptoms. This article presents a case of a 33-year-old male who visited Jeena Sikho Lifecare Limited Hospital, Jodhpur, Rajasthan, on 09/09/2024, with complaints of indigestion, constipation, and body pain. His liver function test showed elevated SGOT and SGPT levels. He had not started any modern medicine. Based on Ayurvedic assessment, he was admitted for Panchakarma therapy followed by a DIP diet. After 16 days of treatment, a positive improvement in LFT values and clinical symptoms was observed.